OPTIMALISASI INSTALASI PENGOLAHAN LUMPUR TINJA DENGAN PENGOMPOSAN LUMPUR TINJA (Studi Kasus IPLT SEMARANG) - Oktiawan, Wiharyanto; Priyambada, Ika Bagus (Universitas Diponegoro, 2007)
Semarang Septage Treatment Facillty is a septage manufacture which serves Semarang Clty distrik. At this moment, the facility is disfunction because the septage pile up in the anaerobic pond. Because of that, Semanng Septage Treatment Facility has to be evaluated which is consisf of technical, infrastructure and management evaluations. As the resulfs of the evaluation, the new anaerobic pond is recomended in 2007, so as the new sludge drying bed in 2005 and 2010. The septage of Semarang Septage Treatment Facility is very huge that is about 3m3/day. The solution that can be taken is composting. The septage is fulfill the compost characteristic after it was dried in 30 days. The management of septage composting are consist of transporation, sifterization, weighing and packaging, and also transportation and storage. Thte price of compos product is Rp. 440,00/kg in 2005 and it will rise to 707,00 in 2014. it is relatively cheap if it is compared with the prices of another fertilizers, so it is proper to sold in the market.